REVITALISASI NILAI-NILAI PERENNIAL DALAM PEMBELAJARAN BAHASA DAN SASTRA: STUDI LITERATUR TERHADAP PENDEKATAN PENDIDIKAN KONTEMPORER - Syamsurijal (STKIP Subang, 2026)
This study explores the revitalization of perennial values in language and literature learning through a literature review of contemporary educational approaches. The transformation of educational paradigms in the digital era has created a dichotomy between instrumental efficiency and substantial depth, generating an urgency to reexamine the relevance of universal timeless values as the epistemological foundation of learning. Employing library research methods with a qualitativedescriptive approach, this research critically analyzes various academic literature from the 2015-2025 period examining the implementation of perennial values in literature learning contexts. Findings indicate that literary works possess intrinsic capacity as a medium for transmitting humanistic values encompassing character, religious-spiritual, and social-ecological dimensions. Implementation of character education through literature learning demonstrates effectiveness in facilitating internalization of fundamental values such as tolerance, honesty, responsibility, and social care through hermeneutic processes of critical reading and in-depth analysis. The religious-spiritual dimension presents a holistic triadic relational framework, while the integration of ecological values demonstrates responses to contemporary environmental crises. The research identifies implementation challenges including learning time constraints and insufficient pedagogical competence among educators. Revitalization of perennial values necessitates the development of structured learning strategies, intensive teacher training, and curriculum reformulation that positions perennial values as core elements of language and literature learning to form holistic and integrated human beings.